Development of a MEMS-based Piezoresistive Cantilever Sensor for Lead (Pb(II)) Detection in Drinking Water - Vankara, Jyothi; Burra, Rajesh Kumar (Engineering, Technology & Applied Science Research, 2024)
One of the most hazardous pollutants of natural water resources is lead -Pb (II)- which poses a significant threat to human health and environmental safety. The accumulation of this heavy metal in an organism affects a number of systems and is particularly dangerous for children. At low levels of intake over short periods, it induces diarrhea, abdominal pain, and renal damage, with the potential for fatal outcomes in extreme cases. The principal sources of lead pollution are industries, coal-fired power plants and motor vehicles. In response to the critical demand for effective lead detection, researchers have developed advanced Micro-Electromechanical Systems (MEMS) piezoresistive cantilever sensors that make use of the chelating properties of Ethylenediaminetetraacetic Acid (EDTA) and the superior electrical properties of reduced Graphene Oxide (rGO). It has been proven that this composite can be effectively immobilized on a MEMS cantilever surface, enabling the selective removal of Pb (II) ions from wastewater. This adsorption process exerts stress on the surface of the cantilever, resulting in variations in resistance that can subsequently be measured. A sensitive and selective MEMS piezoresistive cantilever sensor for Pb (II) has been developed, offering significant potential as a lead monitoring tool in water samples. The sensor demonstrated high sensitivity and selectivity, with a detection limit of 1 ppb and a linear response range of 10-100 ppb. This novel approach has the potential to significantly enhance pollution monitoring and provide substantial benefits for public health by enabling real-time, on-site mapping of lead contamination across aqueous environments. This technological advancement in the environmental surveillance domain offers a new perspective on the safety of water and the reduction of potential health hazards associated with lead consumption.